Constitutive and Relative Facultative Skin Pigmentation among Victorian Children Including Comparison of Two Visual Skin Charts for Determining Constitutive Melanin Density. (19th February 2013) - Pezic, Angela; Ponsonby, Anne‐Louise; Cameron, Fergus J; Rodda, Christine; Ellis, Justine A; Halliday, Jane; Siero, William; Lucas, Robyn M; Dwyer, Terence
Abstract Our aim was to examine the association between ethnicity, phenotype, sun behavior and other characteristics, and constitutive and relative facultative skin pigmentation. A total of 191 participants were recruited, with a mean age of 7.6 years (SD 3.4), during 2009–2011 from Maternal and Child Health Centres (MCHC) and schools in Melbourne, Australia. Parental questionnaire data were obtained on sun behavior and examination consisted of noting the child's natural skin, hair and eye color, ethnicity, nevi count and spectrophotometric melanin density (MD). Constitutive skin pigmentation was estimated from buttock MD. Relative facultative skin pigmentation was estimated by hand compared with buttock absorption. Ethnicity, hair color and skin color were associated with constitutive and facultative skin pigmentation on univariate analysis. Higher ambient ultraviolet radiation (UVR) in the past month, greater freckling, greater nevi and increased sun exposure over the past year were related to darker facultative skin pigmentation. Sun exposure over the life course was not. The two skin charts accounted for 39.7% and 21.4% of buttock MD, respectively. Relative facultative skin pigmentation is associated with recent UVR levels, not life‐course sun exposure. Relative facultative skin pigmentation may not be a useful measure of sun exposure over the early life course. Skin color charts can be used to assess constitutive skin pigmentation if spectrophotometry is not available.